Effectiveness of Ecotourism-Based Field Practicum Model in Improving Scientific Literacy of Prospective Biology Teacher Students - Yamin, Muhammad; Jufri, A. Wahab; Hakim, Aliefman; Gunawan, Gunawan; Riyanto, Andra Ade (Jurnal Pijar Mipa, 2025)
Scientific literacy is an essential competency for prospective science educators in understanding scientific concepts, applying scientific methods, and making decisions based on scientific evidence. This study aims to test the effectiveness of the Ecotourism-Based Field Practicum Model (MPLBE) in improving the scientific literacy of prospective biology teacher students. The subjects of the study were students of the Biology Education study program, FKIP, Mataram University, who took the vertebrate Zoology course. The research design used was a quasi-experiment with a pretest-posttest control group design. The experimental group used the MPLBE model that focused on the study of ecology and conservation of the Megapodius reinwardt bird in the Gunung Tunak and Kerandangan Nature Tourism Parks, while the control group followed conventional practicums in the laboratory. The research instrument was a scientific literacy test that had been validated by experts. Quantitative analysis was performed on the effectiveness of the model using N-Gain and the Mann-Whitney Test. The results of the data analysis showed a significant difference in the increase in scientific literacy scores between the experimental and control groups. These findings indicate that the MPLBE model is effective in improving students' scientific literacy. This model not only strengthens the understanding of biological concepts contextually, but also builds environmental awareness and scientific thinking skills of prospective biology teachers. This study recommends the integration of ecotourism in biology learning as an innovative approach based on local potential.